STANDARDISASI PARAMETER NON SPESIFIK DAN SPESIFIK EKSTRAK ETANOL DAUN JAMBLANG (Syzygium cumini (L.) Skeels) - Maria Ulfah; Ricky Chandra Kurniawan; Metalia Erny (Universitas Wahid Hasyim Semarang, 2020)
ABSTRACT The content of active compounds and the quality of extracts cannot be guaranteed to always be in a constant amount, so it is necessary to standardize. This study aims to prove the ethanol extract of jamblang leaves (Syzygium cumini (l.) Skeels) fulfill the standardization of non-specific and specific parameters as a natural medicine. The ethanol extract of jamblang leaves was extracted by extracting using ultrasonic methods The extract was tested for non-specific parameters including: determination of water content, total ash content, acid insoluble ash content, drying losses and heavy metal contamination. Whereas the specific parameter tests include: identity, organoleptic extract, compounds dissolved in water and ethanol, and chemical content. Test results were analyzed descriptively and compared to standard parameters. The results of non-specific parameters showed a moisture content of 8.04 ± 2.83%, a total ash content of 3.81 ± 1.95%, an acid insoluble ash content of 0.54 ± 0.73%, a drying loss of 9.08 ± 3.01, metal contamination Pb